SUPPRESSING ANXIETY AND IMPROVING ACHIEVEMENT: THE ROLE OF THE ADLX INTROFLEX TERPADU MODEL IN MATHEMATICS LEARNING - Naura Syifa Salsabila; Nanang Supriadi; Indah Resti Ayuni Suri (EMTEKA: Jurnal Pendidikan Matematika, 2026)
Mathematics anxiety is a psychological obstacle that consistently decreases students' motivation and learning achievement, especially at the junior high school level. This study aims to analyze the influence of the Integrated ADLX Introflex model on mathematics learning outcomes and mathematical anxiety of junior high school students in Bandar Lampung. The study used a quantitative approach with a Quasi-Experimental Pretest-Posttest Control Group design, involving 79 students in grade VIII divided into 38 students in the experimental class and 41 students in the control class. The instruments used included a learning achievement test (α = 0.87) and a mathematical anxiety questionnaire (α = 0.89). The data were analyzed using MANOVA after the assumption of normality and homogeneity was met. Partial test results showed F = 56.907 (η² = 0.428) for learning achievement and F = 25.889 (η² = 0.254) for anxiety, both significant at p = 0.000. The MANOVA test yielded Pillai's Trace = 0.522 with p = 0.000, proving that the model had a simultaneous effect on both variables. This model is proven to integrate cognitive, affective, and spiritual dimensions holistically. It is recommended to replicate at different levels and triangulate anxiety instruments psychophysiologically to strengthen the validity of further research. Mathematics anxiety represents a persistent psychological barrier that consistently undermines students' motivation and academic achievement, particularly at the junior secondary level. This study aimed to analyze the effect of the Integrated ADLX Introflex Terpadu model on mathematics achievement and mathematical anxiety among junior high school students in Bandar Lampung. A quantitative approach with a Quasi-Experimental Pretest-Posttest Control Group Design was employed, involving 79 eighth-grade students comprising 38 experimental and 41 control group participants. Instruments included a mathematics achievement test (α = 0.87) and a mathematics anxiety questionnaire (α = 0.89). Data were analyzed using MANOVA following confirmed assumptions of normality and homogeneity. Partial test results yielded F = 56.907 (η² = 0.428) for achievement and F = 25.889 (η² = 0.254) for anxiety, both significant at p = 0.000. MANOVA produced Pillai's Trace = 0.522 at p = 0.000, confirming simultaneous significant effects on both dependent variables. The model effectively integrates cognitive, affective, and spiritual dimensions holistically. Replication across different educational levels and psychophysiological triangulation of anxiety measurement instruments are recommended to strengthen the validity of future research.